2018
DOI: 10.25301/jpda.273.133
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Based Differences in Self-Assessed Reflectionin-Learning Scale

Abstract: ABSTRAT: Reflection heighten students' self-directed and life-long leaning. Gender difference probably represents significant sources of variation in learning behavior which should be detected and identified by medical educationists. This study was accomplished to "compare difference in Reflection-in-Learning Score between the gender and age of dental students in Bolan Medical College, Quetta." METHODOLOGY: An observational quantitative Census was carried out in all professional year dental students (n=85) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…This follows research from Wallman, Lindblad, Gustavsson, & Ring (2009), which found that gender did not affect reflection. In contrast to the results of research from Khan, Saeed, Yasmin, Butt, & Khan (2018) found that the female sex was more reflective than the male. Based on age, both the age groups of 21 -22 years, 23 -26 years, and 25 -26 years both have high critical reflective work behaviour.…”
Section: Resultscontrasting
confidence: 72%
“…This follows research from Wallman, Lindblad, Gustavsson, & Ring (2009), which found that gender did not affect reflection. In contrast to the results of research from Khan, Saeed, Yasmin, Butt, & Khan (2018) found that the female sex was more reflective than the male. Based on age, both the age groups of 21 -22 years, 23 -26 years, and 25 -26 years both have high critical reflective work behaviour.…”
Section: Resultscontrasting
confidence: 72%
“…1,24 Girls are prominent in these tasks due to their high will power, persistent struggling quality and maturity proving to be in the lead. 25 On the other hand, Grant A and Sobral DT both researchers did not find any difference between gender and learning approach in their scientific research work. 8,9,11…”
Section: Discussionmentioning
confidence: 91%
“…Hasil penelitian yang dilakukan oleh Khan et al menunjukkan bahwa perempuan dan usia diatas 20 tahun memiliki tingkat refleksi diri yang lebih tinggi. 13 Selain itu, tingkat kemampuan refleksi diri juga dapat dipengaruhi oleh nilai atau performa akademik seseorang, motivasi dan respons dari pengajar. 3 Refleksi diri merupakan kemampuan yang harus dimiliki seorang dokter.…”
Section: Pendidikanunclassified